PERAN KOLEKSI DIGITAL PERPUSTAKAAN IAIN KEDIRI DALAM MENINGKATKAN LITERASI MAHASISWA - Moch. Basit Aulawi (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This study aims to describe and analyze the role of digital collections managed by the IAIN Kediri Library in improving information literacy among students. In the era of information disruption, libraries function not only as repositories of physical books but also as providers of technology-based knowledge access. This study used a qualitative descriptive approach. Data were collected through direct observation of the library's digital services, in-depth interviews with librarians, and the distribution of questionnaires to students as service users. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that the IAIN Kediri Library's digital collections, which include e-books, e-journals, and institutional repositories, play a significant role as a catalyst for student learning independence. Flexible accessibility (accessible anytime and anywhere) has been shown to increase students' frequency in searching for scientific references. However, the effectiveness of this literacy improvement is also influenced by students' technical abilities in filtering information. It was found that the availability of digital collections encourages students to be more critical in evaluating data sources, although technical constraints such as network stability and understanding of search features remain minor obstacles. It can be concluded that the IAIN Kediri Library's digital collection plays a vital role in enriching students' knowledge and improving their literacy standards. Optimizing services through more intensive outreach and developing digital platform interfaces is recommended to maximize the collection's benefits to the academic community.